Clima Organizacional y desempeño laboral de los colaboradores de la empresa Electro Oriente, año 2021 - Davila Reategui, Maria Elena Celeste (2022)
The objeive of this research is to determine the relationship of the organzatinal climate with job performance in Electro Oriente, year 2021, thtype of quantitative, non-experimental, descriptive and correlational research was used, the population is made up of all employee of the company Electro Oriente, in the year 2021, the survey was carried out on a sample of 40 employees of the company, as a result there is a significant correlation of moderate degree with a Pearson correlation value equal to 0.454 and a sigma value (bilateral) equal to 0.003. When analyzing the dimensions of variable 1: Orgnizational climate, we determined that more than 50% of workers are indifferent to the way in which the dimensions of the organizational climate are developed, buy they feel more involved with the dimensions of work performance, finally we can affirm although the organizational climate variable is related to job performance, its degree of relationship is not high, so, in general workers are focused on showing good job performance without paying much attention to the factors that determine an optional organizational climate.